Overconfidence and the political and financial behavior of a representative sample - Steffen Ahrens; Ciril Bosch-Rosa; Bernhard Kassner (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2021)
We study the relationship between overconfidence and the political and financial behavior of a nationally representative sample. To do so, we introduce a new method of eliciting overconfidence that is simple to understand, quick to implement, and captures respondents' excess confidence in their own judgment. Our results show that, in line with theoretical predictions, an excessive degree of confidence in one's judgment is correlated with lower portfolio diversification, larger stock price forecasting errors, and more extreme political views. Additionally, we find that overconfidence is correlated with voting absenteeism. These results appear to validate our method and show how overconfidence is a bias that permeates several aspects of peoples' life.
Keywords: C83; D91; G41; 330; Overconfidence; SOEP; Survey